Pengaruh Sosial Media, Influencer dan Customer Review Terhadap Keputusan Pembelian Produk Ms Glow - Narista, Falikhaturrohma Dian; Himawan, Abdurrahman Faris Indriya (Jurnal Mahasiswa Manajemen, 2021)
Background - In this modern era, cosmetics are no longer a desire for a consumer but have become a daily necessity for humans. Dressing up can make them appear more confident. In Indonesia, the cosmetics business is a promising business opportunity, so it’s no wonder that many companies are successful with their cosmetic products. Cosmetics sales are not inferior to other sales in following technological developments. Objective - To analyze the influence of social media, influencers and customer reviews on customer purchasing decisions for Ms. Glow’s cosmetic products. Design/Methodology/Approach - This research examines the influence of social media, influencers and customer reviews on the decision to purchase Ms Glow product with 95 samples of Ms Glow customers have an Id Card, get data through distributing questionnaires to them and for testing using multiple linear regression analysis with SPSS. Findings - Social media and influencer variables had an effect on the purchase decision for Ms Glow’s products, while the customer reviews had no effect on the consumer purchasing decisions Ms Glow. Research implications - This research can be used as a reference for viewing and seeking information on social media, influencers and customer reviews of consumer purchasing decisions for Ms Glow products. Research limitations - In this modern era, customer reviews should be very influential on consumer purchasing decisions because they are done easily, but this research is the opposite with possible answers because they’re confident and have customer loyalty to Ms. Glow’s products.